MODERASI PENDIDIKAN ISLAM STUDI KASUS BUMRUNG SUKSA ISLAMIC SCHOOL DI THAILAND SELATAN - Saifiyatil Bashiroh; Ahmad Khumaidi; Ummi Lailia Maghfiroh (Jurnal Visi Ilmu Pendidikan)
Islamic education in Southeast Asia has its own dynamics and challenges, especially in countries with a majority non-Muslim population. One interesting case study is Bumrung Suksa Islamic School in Southern Thailand, an Islamic educational institution that has adapted to global dynamics and contemporary demands. This research uses a qualitative approach to explore the concept of moderation in Islamic education in this school. This approach involves in-depth interviews with teaching staff, students and school stakeholders, as well as analysis of documents related to the school’s curriculum and policies. The research results show that Bumrung Suksa Islamic School has succeeded in integrating Islamic values of moderation into their daily education. This school’s curriculum not only focuses on the transfer of religious knowledge, but also on character formation, developing a balanced understanding of Islam, strengthening an Islamic identity that is balanced with tolerance and openness, as well as inter-ethnic dialogue that strengthens harmonious relations between members of the school community. It is hoped that this research can contribute to the global Islamic education literature, especially in the context of Muslim minority communities in non-Muslim countries. Through a better understanding of the moderation of Islamic education, it is hoped that educational models that are relevant and effective in responding to the complex dynamics of the modern era can be found. Keywords : Islamic Education, Moderation, Global Adaptation, Character, Identity, Inter-ethnic Dialogue, Community Harmony. Abstrak Pendidikan Islam di Asia Tenggara memiliki dinamika dan tantangan tersendiri, terutama di negara-negara dengan mayoritas penduduk non-Muslim. Salah satu studi kasus menarik adalah Bumrung Suksa Islamic School di Thailand Selatan, sebuah lembaga pendidikan Islam yang telah beradaptasi dengan dinamika global dan tuntutan kontemporer. Penelitian ini menggunakan pendekatan kualitatif untuk mengeksplorasi konsep moderasi pendidikan Islam di sekolah ini.Pendekatan ini melibatkan wawancara mendalam dengan staf pengajar, siswa, dan pihak terkait sekolah, serta analisis dokumen terkait kurikulum dan kebijakan sekolah. Hasil penelitian menunjukkan bahwa Bumrung Suksa Islamic School telah berhasil mengintegrasikan nilai-nilai moderasi Islam dalam pendidikan sehari-hari mereka.Kurikulum sekolah ini tidak hanya memfokuskan pada transfer pengetahuan agama, tetapi juga pada pembentukan karakter, pengembangan pemahaman yang seimbang terhadap Islam, penguatan identitas Islam yang seimbang dengan toleransi dan keterbukaan, serta dialog antar-etnis yang memperkuat hubungan harmonis di antara anggota komunitas sekolah.Penelitian ini diharapkan dapat memberikan kontribusi pada literatur pendidikan Islam global, khususnya dalam konteks masyarakat minoritas Muslim di negara-negara non-Muslim. Melalui pemahaman yang lebih baik tentang moderasi pendidikan Islam, diharapkan dapat ditemukan model pendidikan yang relevan dan efektif dalam menjawab dinamika kompleks zaman modern. Kata Kunci : Pendidikan Islam, Moderasi, Adaptasi Global, Karakter, Identitas, Dialog Antar-etnis, Harmoni Komunikasi